2019
DOI: 10.1123/ijspp.2018-0110
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-Volume, High-Intensity Training on Performance Parameters in Competitive Youth Swimmers

Abstract: A 7 week HIT intervention was neither beneficial nor detrimental to performance parameters however the HIT group completed 6 hours (17.0-km) swimming per week compared to 12 hours (33.4-km) per week for the HVT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
(49 reference statements)
2
14
2
1
Order By: Relevance
“…Full-text evaluations were done for the remaining 61 studies, and 45 studies were excluded because of the following reasons: no appropriate control (n = 33), no desirable outcomes (n = 6), and no RCT design (n = 6). After this, a total of 16 RCTs were considered eligible and included in the final meta-analysis [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. No new eligible trial was identified by manual searching of the reference lists of retrieved studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Full-text evaluations were done for the remaining 61 studies, and 45 studies were excluded because of the following reasons: no appropriate control (n = 33), no desirable outcomes (n = 6), and no RCT design (n = 6). After this, a total of 16 RCTs were considered eligible and included in the final meta-analysis [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. No new eligible trial was identified by manual searching of the reference lists of retrieved studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of USRPT as a new and alternative training methodology has resulted in a large amount of controversy in the swimming community. [18][19][20][21][22][23][24] The notion that low-volume training at high intensities (USRPT or HIT) may be a more beneficial training methodology than HVT, often coinedthe "Quality versus Quantity" debate, is a long-standing topic of discussion among swimming coaches. 18,23,114 While there are potential benefits to USRPT, the findings of the systematic review indicate that there is currently no peer-reviewed published literature of USRPT interventions on competitive swimmers.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to suggest that USRPT is a derivative of HIT, 69,82 and there is peer-reviewed published literature to support the benefits of HIT in competitive swimmers. 22,27,73,[90][91][92][93][94] However, national and international level swimmers competing in sprint to distance events have been found to perform around 6-16% of their training as HIT 30,71 which is similar to the training patterns of other cyclical sports. 25,69,70 The remainder of their training comprises a variety of stimuli: LIT, MIT, RT and cross-training activities, of which there is a large amount of published literature to support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations